The content validity of the ANMS GCSI-DD in patients with idiopathic or diabetic gastroparesis - Revicki, Dennis A. (J Patient Rep Outcomes, 2018)
BACKGROUND: The American Neurogastroenterology and Motility Society Gastroparesis Cardinal Symptom Index-Daily Diary (ANMS GCSI-DD) was developed to meet Food and Drug Administration (FDA) recommendations for patient-reported outcome (PRO) endpoints in gastroparesis studies, including therapeutic trials. The current version of the ANMS GCSI-DD contains five items pertaining to nausea, early satiety, post-prandial fullness, upper abdominal pain, and vomiting. The specific aims of this study were to determine if the appropriate symptoms are included in the ANMS GCSI-DD and to assess the content validity in patients with idiopathic (IG) and diabetic gastroparesis (DG). METHODS: Patients diagnosed with IG or DG were recruited by five clinical sites in the United States for a cross-sectional, qualitative study involving one-on-one in-person concept elicitation and cognitive debriefing interviews. Concept elicitation included open-ended questions to elicit patients’ symptoms and impacts of gastroparesis, while cognitive debriefing was designed to assess the comprehensiveness of the ANMS GCSI-DD and clarity of the instructions, items, and response scales. The interviews were audio-recorded and transcribed. Transcripts were analyzed using a content analysis approach with ATLAS.ti. RESULTS: Of 25 patients interviewed, 15 (60%) had IG and 10 (40%) DG. Mean age of the sample was 42.3 years (range: 20–70 years), and most patients were female (n = 19, 76%) and white (n = 19, 76%). During concept elicitation, patients endorsed the following signs and symptoms as relevant and important to their condition: early satiety (n = 25, 100%), post-prandial fullness (n = 25, 100%), nausea (n = 22, 88%), upper abdominal pain (n = 18, 72%), vomiting (n = 15, 60%), and bloating (n = 11, 44%). Many patients (n = 20, 80%) experienced day-to-day symptom change. During cognitive debriefing, patients confirmed the ANMS GCSI-DD content was comprehensive and reflective of their gastroparesis experience. Patients could easily select a response option and describe how they arrived at their answers. Overall, patients found the instrument’s instructions, recall period, items, and response options clear and understandable. CONCLUSIONS: The ANMS GCSI-DD was easily understood, found to contain the most important symptoms for patients with IG and DG, and no changes were recommended. Results support the content validity of the ANMS GCSI-DD for clinical trials and clinical care among IG or DG patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s41687-018-0081-2) contains supplementary material, which is available to authorized users.